2011
DOI: 10.1523/jneurosci.6809-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Short Bouts of Vocalization Induce Long-Lasting Fast Gamma Oscillations in a Sensorimotor Nucleus

Abstract: Performance evaluation is a critical feature of motor learning. In the vocal system, it requires the integration of auditory feedback signals with vocal motor commands. The network activity that supports such integration is unknown, but it has been proposed that vocal performance evaluation occurs offline. Recording from NIf, a sensorimotor structure in the avian song system, we show that short bouts of singing in adult male zebra finches (Taeniopygia guttata) induce persistent increases in firing activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 72 publications
2
33
0
Order By: Relevance
“…Multiunit activity is generally strongest shortly before and during syllable production and weakest during the times corresponding to silent intervals between syllables. Lewandowski and Schmidt (2011) quantified multiunit motor activity in NIf and found that it precedes the onset of song introductory notes by an average 45.7 ± 15.7 ms, which is remarkably similar to the song premotor onset value of 45 ms reported for HVC (Schmidt, 2003; Kozhevnikov and Fee, 2007). Consistent with the idea that activity in NIf during song production is motor and not auditory related, vocalization-related multiunit activity in NIf ends 26.5 ± 13.5 ms before vocal offset, and this cessation of premotor activity is accompanied by a general suppression of neuronal activity in NIf (Fig.…”
Section: Motor and Motor-related Neural Activity In Nifsupporting
confidence: 67%
See 2 more Smart Citations
“…Multiunit activity is generally strongest shortly before and during syllable production and weakest during the times corresponding to silent intervals between syllables. Lewandowski and Schmidt (2011) quantified multiunit motor activity in NIf and found that it precedes the onset of song introductory notes by an average 45.7 ± 15.7 ms, which is remarkably similar to the song premotor onset value of 45 ms reported for HVC (Schmidt, 2003; Kozhevnikov and Fee, 2007). Consistent with the idea that activity in NIf during song production is motor and not auditory related, vocalization-related multiunit activity in NIf ends 26.5 ± 13.5 ms before vocal offset, and this cessation of premotor activity is accompanied by a general suppression of neuronal activity in NIf (Fig.…”
Section: Motor and Motor-related Neural Activity In Nifsupporting
confidence: 67%
“…At the multiunit level, motor activity in NIf, HVC, and RA is broadly similar (Yu and Margoliash, 1996; Schmidt, 2003; Kozhevnikov and Fee, 2007; Lewandowski and Schmidt, 2011). Unlike single unit activity, multiunit activity in all three of these nuclei is characterized by increases in neural activity that precede vocal output and continue throughout song (Fig.…”
Section: Motor and Motor-related Neural Activity In Nifmentioning
confidence: 99%
See 1 more Smart Citation
“…The multitaper estimate is among the most reliable nonparametric spectral estimation methods. The foregoing method of estimating the PSD of the smoothed PSTH, which we denote by PSTH-PSD, is one of the most commonly-used methods for extracting the spectral representation of the spiking data [11,12,13]. We have considered a frequency spacing of 0.125Hz for the PSD estimates here, which corresponds to N = 1200 in our proposed method, and DC components of the normalized PSD's are eliminated in the figures.…”
Section: Application To Simulated and Real Datamentioning
confidence: 99%
“…Following the common frequency-domain analysis of neural data such as EEG, existing methods for point process spectral estimation often compute a continuous estimate of the spiking rate and analyze the power spectral density (PSD) of this estimate. The spiking rate estimation is either done by simply smoothing the spiking histogram [11,12,13] or using generalized linear Gaussian state-space models to estimate the conditional intensity function (CIF) of the point process [14,15]. However, these approaches suffer from the following shortcomings: Firstly, they are limited in terms of their spectral resolution as smoothing in the time domain for spiking rate estimation results in distortion in the frequency domain.…”
Section: Introductionmentioning
confidence: 99%